Memory of the Covid Pandemic. Reflection from a Philosophical Anthropology - Anrubia Aparici, Enrique; Gaona Pisonero, Carmen (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
From an anthropological approach and a scholar framework of visual archaeology, this article tries to question -ask and answer- about the status, causes and effects that the "visual remains" of the lockdown of the Pandemic caused in the Spanish-speaking world and, particularly in Spain. The underlying question is whether these “visual remains” can be considered “spaces of resistance” -mostly collective-, or if, on the other hand, they have been framed within other interpretive frameworks, such as spaces of pain, spaces of hope, etc.